Efeitos da obesidade em camundongos sobre a expressão e extinção de respostas aversivas no teste de medo condicionado ao contexto - Rafaela Pinto Coelho Santos (2019)
The obesity is a public health problem associated with the development of several comorbidities, including anxiety and depression. Obesity is also a result of the exacerbated expansion of adipose tissue, which modifies the homeostasis of the organism inducing a chronic and low-grade systemic inflammatory response. The increase of peripheral pro-inflammatory cytokines promotes the activation of the immune system and possibly, neuroinflammation in the central nervous system (CNS). Consequently, there is an increase of Nitric Oxide (NO) mainly released from the activation of inducible nitric oxide synthase (iNOS). The excess of NO in the CNS is also associated with anxiety disorders and post-traumatic stress disorder (PTSD). The goal of this study was to investigate the influence of obesity in the expression and extinction of aversive memory in fear conditioning context test (FCCT), and subsequent role of NO, via iNOS. Two models of obesity were employed: a genetic mouse model with leptin receptor mutation (db/db), and also an obesity model induced by consumption of cafeteria diet (DCaf) for 4 weeks. All animals were submitted to FCCT. where an aversive stimulus (three randomized shocks, with intensity of 0.3mA and duration of 2s) was paired with a neutral stimulus (conditioning box). After 24 hours (Day 1 – Test), animals were re-exposed to the box for 5 minutes and the time of immobility was determined. To evaluate the extinction of the aversive memory, the animals were re-exposed to the conditioning box for three days with a 48-hour interval (Days 3, 5 and 7). In order to investigate the role of iNOS on the behavioral changes, an iNOS inhibitor was administered via i.p. 30 minutes prior to the FCCT. The results suggest that the cafeteria diet induced obesity in the animals. However, we also observed two different profiles on behavior response in the FCCT: In the first experiment, DCaf fed animals displayed an increase in the immobility time as compared to the control group. Although the same effect was not observed in the subsequent experiment. The pre-treatment with iNOS inhibitor aminoguanidine (50 mg/kg) did not alter the freezing behavior of the animals. Thus, it would be possible to suggest that other factors such as: genotype, remodeling of adipose tissue, microbiota and climate, might be associated to the data obtained. The db/db mice exhibited anxiogenic-like behavior and impairment in the extinction of aversive memory. Moreover, the acute pre-treatment with iNOS inhibitors (aminoguanidine 50 mg/kg and 1400W 0.5 μg/kg) did not change this response.